Lane’s Masonic Records - The Library and Museum of Freemasonry (2020)
"John Lane’s Masonic Records 1717-1894 is an authoritative listing of all the lodges established by the English Grand Lodges from the foundation of the first Grand Lodge in 1717 up until 1894. It was published by the United Grand Lodge of England in 1895 and proved to be a very useful reference book for anyone with an interest in freemasonry under any of the English Grand Lodges. Masonic Records enables the early history of freemasonry in a particular place to be readily traced and provides information about individual lodges." [self-description]